THE LEADERSHIP ROLE OF FEMALE SCHOOL PRINCIPALS IN RURAL STATE HIGH SCHOOLS - Ruby Santamoko (International Journal of Teaching and Learning, 2024)
Women's leadership is still a pro and a con in the public sphere. Even though they have become leaders, women's ability to lead is still underestimated. In relation to school culture, principals who are successful in advancing the school are seen from their ability to develop a conducive organizational culture. A conducive organizational culture influences student achievement. So, it can lead to achieving the school's vision, mission and goals. The inhibiting factors that influence the leadership of female school principals are: 1) the domestic role of women, 2) gender stereotypes, 3) physical barriers, and 4) patriarchal culture, which are cultural factors that are deeply rooted and ingrained in the culture of our society. In society, culture still considers that domestic affairs are women's territory. So even though women work outside and are principals, women still have to carry out their responsibilities in the household, such as cooking, washing and as mothers and wives. This is what ultimately makes women who work end up having multiple roles that are heavier than men's responsibilities.